Draft Annual Plan 1986-87 Review and Outline Volume-I Government of Manipur - Planning Commission (Planning Commission, 1986)
Manipur is one of the smallest state located in the eastern most part of the country. the state has an area of 22,327 sq. kms., an area which constitutes about 0.7% only of the total land surface of the Indian Union. of the total area, 20089 sq. kms. are in the hill and it constitutes 90% of the total area. This beautiful mountainous state is famous for her salubrious climate, colourful dances, handloom and handicraft products.
Planning Department, Govt. of Manipur